Geographic and Seasonal Variation in Species Diversity and Community Composition of Frugivorous Drosophila (Diptera: Drosophilidae) and their Leptopilina (Hymenoptera: Figitidae) Parasitoids. Issue 5 (29th August 2018) - Lue, Chia-Hua; Borowy, Dorothy; Buffington, Matthew L; Leips, Jeff
Abstract: Many studies have investigated species diversity patterns across space and time, but few have explored patterns of coexistence of tightly interacting species. We documented species diversity patterns in a host–parasitoid system across broad geographic location and seasons. We calculated species diversity (H and e H    ′ ) and compared the relationship between community similarity and geographic distances of frugivorous Drosophila host (Diptera: Drosophilidae) and Leptopilina parasitoid (Hymenoptera: Figitidae) communities across Eastern North America, from New Hampshire to Florida, at two time points during the breeding season. We also analyzed the influence of environmental factors on species assemblages via constrained correspondence analysis and lastly calculated cluster dendrograms to identify potential host–parasitoid interactions. We found that the composition of Drosophila – Leptopilina communities varied significantly with latitude. Interestingly, diversity increased with increasing latitude, a trend counter to latitudinal patterns of diversity observed in many other taxa. We also found seasonal effects of monthly temperature range and precipitation on host biodiversity patterns across geographic locations. Cluster dendrograms nominated potential parasitoid–hosts and competitive interactions to be validated in the future studies. The present study fills an important gap of knowledge in North American Drosophila–Leptopilina species diversity patterns and lays the groundwork for future ecological and evolutionary studies in this system.